2019
DOI: 10.1177/0958305x19882373
|View full text |Cite
|
Sign up to set email alerts
|

The long-run environmental impacts of economic growth, financial development, and energy consumption: Evidence from emerging markets

Abstract: In this study, the long-term interactions between carbon dioxide (CO2) emissions, real gross domestic product, fossil fuel consumption, and financial development are examined for 15 emerging markets during 1980–2014 by using heterogeneous dynamic panel data techniques. Long-run elasticity results show that the environmental Kuznets curve hypothesis is not valid for emerging markets. Besides, long-run findings reveal that fossil fuel energy consumption has a powerful negative impact on the environmental quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 122 publications
(149 reference statements)
1
17
2
Order By: Relevance
“…Similar findings are also confirmed by Acheampong (2019), Cetin and Bakirtas (2020), Kayani et al (2020), Le et al (2020), Shoaib et al (2020), Tamazian and Rao (2010), Wang et al (2020a), andYin et al (2019). The third strand of literature implies that no significant linkage exists between financial development and CO 2 emissions.…”
Section: Literature Reviewsupporting
confidence: 66%
See 1 more Smart Citation
“…Similar findings are also confirmed by Acheampong (2019), Cetin and Bakirtas (2020), Kayani et al (2020), Le et al (2020), Shoaib et al (2020), Tamazian and Rao (2010), Wang et al (2020a), andYin et al (2019). The third strand of literature implies that no significant linkage exists between financial development and CO 2 emissions.…”
Section: Literature Reviewsupporting
confidence: 66%
“…Brazil, Russia, India, and China); and Ziaei (2015) for European, East Asian, and Oceania countries. In addition to country and regional levels, some scholars have explored the relationship between these two variables at the global level, including Acheampong et al (2020) for 83 countries; Cetin and Bakirtas (2020) for 15 emerging markets; Ehigiamusoe and Lean (2019) for 122 countries; Dogan and Seker (2016) for the top renewable energy countries; Kayani et al (2020) for the top ten CO 2 emitter countries; Nasreen and Anwar (2015) for 59 countries; Renzhi and Baek (2020) for 103 countries; and Tamazian and Rao (2010) for 24 transition economies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While, the carbon intensity is elaborated as the carbon emission released due to per unit of energy use for particular economic activities (industrial production process, etc.). Cetin and Bakirtas 15 has confirmed a positive association between financial development and carbon emission, energy consumption and carbon emission. Wu 16 confirmed asymmetric effect of non-clean energy on economic growth.…”
Section: Introductionmentioning
confidence: 89%
“…With the aim of investigating the effect of domestic credit and manufacturing activities on CO 2 emissions, the study controls for income and urbanization [which studies such as Asane-Otoo (2015) and Cetin and Bakirtas (2019) have shown that they affect CO 2 emissions and are also crucial in South Africa] and therefore models CO 2 emissions as a function of income, urbanization, domestic credit and manufacturing:…”
Section: Empirical Modelingmentioning
confidence: 99%
“…In other studies, Yasin et al (2020) focused on 110 developed and developing countries and noted that financial development destroys the environment of developed countries but it improves the quality of the environment for developing countries. Cetin and Bakirtas (2019) found income and trade to reduce CO 2 emissions while urbanization, fossil fuel and financial development increased CO 2 emission for emerging markets. York and McGee (2017) found for a group of 128 countries that income and manufacturing increase CO 2 emission while renewable energy reduces it.…”
Section: Introductionmentioning
confidence: 99%